Analisis Komparatif Kerangka Merdeka Belajar Sebagai Sarana Untuk Mencapai Deep Learning Pada Siswa Sekolah Dasar: Sebuah Kajian Pustaka: A Comparative Analysis of the Merdeka Belajar Framework as a Means to Achieve Deep Learning in Elementary School Students: A Literature Review - Sappaile, Baso Intang (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Contemporary education demands a shift from surface learning to deep learning, which focuses on conceptual understanding and critical thinking. In Indonesia, the Kurikulum Merdeka (Merdeka Curriculum) has been introduced as a new framework that philosophically aligns with this objective. This study aims to conduct a comparative analysis of the Merdeka Curriculum framework as a vehicle for achieving deep learning among elementary school students. The method employed is a literature review, analyzing secondary data from scientific journals, government policy documents, and other relevant literature. The data is analyzed qualitatively to identify convergences and potential gaps. The results of the analysis indicate a strong alignment between the two concepts. Specifically, (1) Differentiated Learning within the Merdeka Curriculum directly facilitates the attainment of conceptual understanding; (2) the Project to Strengthen the Pancasila Student Profile (P5) serves as an effective arena for developing the core competencies of deep learning (the 6Cs); and (3) the emphasis on formative assessment promotes the development of students' metacognitive skills. Nevertheless, a major critical point is identified at the implementation level, where the success of this transformation is highly dependent on the capacity and pedagogical understanding of teachers. It is concluded that the Merdeka Curriculum holds significant potential as a vehicle for deep learning, yet it requires support through professional development for teachers that focuses on strengthening higher-order cognitive learning strategies.